The Reve’s Puzzle with Relaxation of The Divine Rule: The Reve’s Puzzle with Relaxation - Majumdar, Abdullah-Al-Kafi (Proceedings of the Pakistan Academy of Sciences: A. Physical and Computational Sciences, 2021)
This paper considers a variant of the Reve’s puzzle with n ( >1) discs which admits of r ( >1) number of violations of the “divine rule”. Denoting by S4(n, r) the minimum number of moves required to solve the new variant, we give a scheme to find the optimality equation satisfied by S4(n, r). We then find an explicit form of the optimal value function S4(n, r).